Almacenamiento de carbono por clase diamétrica y en necromasa en aguajales mixtos de la comunidad de Miraflores Río Napo, Mazán-Perú, 2018 - Rengifo Tuesta, Damaris Adela (2021)
The study was conducted in the Miraflores community, in a mixed aguajal, with the aim of determining carbon storage by diameter class, species, and in necromass. The study was observational, quantitative, deductive, and field-based. It evaluated 87 individuals corresponding to Quararibea wittii (37), Mauritia flexuosa (26), Coussapoa trinervia (9), Virola pavonis (7), Mauritiella aculeata (4), Garcinia macrophylla (2), Callophyllum brasiliense (1), and Euterpe precatoria (1). The total carbon stored in tree species was 13.54 t.C/ha, with Mauritia flexuosa (5.50 tC/ha) and Quararibea wittii (4.84 t.C/ha) having the highest storage in the diameter classes of 30-<40 and 20-<30, respectively. The total carbon stored in necromass was 6.65598 tC/ha. Statistical analysis using the Kruskal-Wallis and Bonferroni tests revealed significant differences in carbon storage across all diameter classes and the species that make up the mixed aguajal.